Analysis of the educational policy management of the Chilean Ministry of Education based on teacher, student and leader perception surveys - López Arias, Katherine (Contextos Educativos. Revista de Educación, 2014)
This research seeks to know the perceptions of integrating agents about the school management quality policies applied at a High School in the city ofPunta Arenas, Magellan and Antarctic Region. Thus, the Chilean educational policies and the concept of quality are dealt with. It is non-experimental, quantitative-qualitative descriptive study, approached from a mixed paradigm that analyzes this high school’s management regarding the educational policies set forth by the Chilean Ministry of Education. For the quantitative approach a student and teacher survey is applied, whereas for the qualitative part an interview to the integrating agents (students, teachers, leaders and parents) is carried out. As a result, it is concluded that the ministry’s educational policies are integrated in this high school’s Institutional Development Plan. However, in practice, not all members of this educational community participate in the decision-making process, as its Strategic Plan does not take the interests of this educational community into account. El presente estudio busca conocer las percepciones de los agentes integrantes acerca de las políticas de mejoramiento de la calidad de la gestión escolar de un establecimiento educacional de la Comuna de Punta Arenas. En este contexto, se aborda principalmente las políticas educativas y el concepto de calidad en Educación. Se trata de una investigación, con un diseño no experimental de carácter descriptivo, abordada desde la complementariedad paradigmática, y que busca analizar la gestión escolar en el marco de la aplicación de las políticas educativas emanadas del Ministerio de Educación de Chile (MINEDUC). Para el enfoque cuantitativo se emplea un cuestionario de estudiantes y otro de docentes, mientras que la parte cualitativa se realiza mediante una entrevista a los agentes integrantes (estudiantes, docentes, directivos y apoderados). A partir de los resultados se concluye que, efectivamente, las políticas ministeriales son parte de la definición de políticas del ...